Do the coaches adapt to tournament importance? Strategic choice of starting squads in national football teams - Avkhimovich, N. (Journal of Sports Economics, 2026)
The paper examines coaches` strategic choices in selecting starting squads of national football teams for tournaments with different levels of importance. Building on age-related human development, resilience, and team diversity theories, it empirically studies several regression models of coaches` strategic choices regarding the starting squad`s average age and age diversity. Using match-level data from 32 European national football teams and more than 3,000 matches from 2014-2023, the analysis covers different competitions: friendly matches, continental championships (the UEFA EURO), and the FIFA World Cup. The results show that coaches have differentiated strategies for the starting squad`s average age across tournaments with different importance. The average age of the starting squad for the final and qualification stages of the FIFA World Cup and UEFA EURO, the most important tournaments, is up to 0.8 years higher than for a friendly match. The paper also shows that the age diversity of the starting squad varies depending on the tournament the national team participates in, being 4 - 6% higher for the final stages of the FIFA World Cup and UEFA EURO compared with friendly matches. However, none of the age-related parameters lead to a significant improvement in the probability of winning an individual match. Such an effect could be explained by coaches` perceived importance, as well as coaches` anchoring toward more experienced players.